PARTISIPASI MAYARAKAT DALAM PENGEMBANGAN OBJEK WISATA DI KAWASAN BUDAYA SARIBU RUMAH GADANG DI KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN. - Mimi Yulia putri Mimi; Ahyuni ahyuni (JURNAL BUANA, 2021)
ABSTRACT This study aims: (1) Knowing the process of the formation of tourist objects (2) promoting community involvement and (3) financial benefits. This type of research is a qualitative descriptive study. The research subjects were taken through purposive sampling technique so that 34 informants were obtained. The method used by the author in this research is primary data in the form of data obtained directly and interviews and secondary data in the form of journals. The results showed: (1) The process of forming a tourist attraction began in 2011 after the making of a film entitled Under Protection of the Ka'bah, since the making of the film, an idea emerged from Mr. Musrullah as the Lelo Panjang and invited Ibuk Susilawati and Ibuk. Yusni and the Malay Tribe, Ninik Mamak, to conduct deliberations to be able to develop this tourist attraction in various ways, such as carrying out Halal Bihalal among you, the Malay tribe by holding traditional art events, traditional dances, traditional speeches and traditional music, so that with this kind of event can attract the attention of tourists to be able to visit tourist attractions in the Saribu Rumah Gadang Cultural area. (2) The propagation of community involvement in the tourism object in the Saribu Rumah Gadang Cultural area starts from the individual, POKDARWIS (tourism awareness group) of the Bundo Kanduang, managers, the Lelo Panjang, the Tourism and Community Service. (3) The financial benefits received by the community are very large (estimated at approximately Rp. 1,000,000-2,000,000 million per month) with the increasing number of tourists visiting the Saribu Rumah Gadang area, the more income and the economy and the increasing received by the public from the number of tourists who visit. Keywords: Community Participation, Tourism Objects